Liver tissue sparing resection using a novel planning tool - Pianka, Frank; Baumhauer, Matthias; Stein, Daniel; Radeleff, Boris; Schmied, Bruno; Meinzer, Hans-Peter; Müller, Sascha A. (Langenbeck's archives of surgery, 2011)
PURPOSE: Accurate preoperative prediction of liver function, volume, and vessel anatomy is essential in preventing postoperative liver failure, optimizing safety, and ensuring optimal outcome in patients undergoing hepatic surgery. We propose that preoperative resection planning provides useful anatomical and volumetric data, allowing for sparing of liver tissue in surgical resections. The purpose of the present study was to evaluate the use of a novel resection planning tool. - METHODS: Thirteen patients undergoing hemihepatectomy were included. Preoperative resection planning was performed using the commercially available software Mint Liver. During resection planning, virtual resections were calculated based on Couinaud classification, Cantlie's line (standard), and individually by the operating surgeon (individual). Intraoperatively, volume and weight of the resected specimen were measured. A 14-day follow-up was conducted, and laboratory parameters were collected. Statistical analysis was performed, comparing virtual resection volumes (i.e., standard vs. individual) and secondarily virtual vs. actual resection volume. - RESULTS: We found a significant difference (p = 0.001) in the comparison of standard vs. individual in all 13 cases, with an average 92.8 mL smaller resected volume, sparing 11.3% of liver parenchyma with virtual resection. No patients suffered from acute liver failure. Perioperative mortality was 0%. - CONCLUSION: Mint Liver is capable of acquiring exact anatomical and volumetric knowledge prior to hepatic resections. Liver parenchyma can be spared by preoperative assessment of the resection plan. We propose that this tool could be an important addition to preoperative patient evaluation, especially in complex liver surgery and living donor liver transplantation where precise volumetry is the decisive factor.